Intravenous magnesium sulfate versus intravenous meperidine to prevent shivering during spinal anesthesia (Medical Journal of Indonesia, 2022)
BACKGROUND Shivering is a frequent event during neuraxial anesthesia due to impaired central and peripheral thermoregulation control. Meperidine and MgSO4 are effective in lowering the shivering threshold. Hence, this study aimed to compare the efficacy of MgSO4 and meperidine to prevent shivering in patients undergoing spinal anesthesia. METHODS This was a double-blind randomized clinical trial of 100 patients divided into 2 groups. One group had MgSO4 30 mg/kg, and the other group had meperidine 0.5 mg/kg intravenously in 100 ml of 0.9% NaCl before undergoing spinal anesthesia. Participants were non-pregnant patients aged 18–65 years and had physical status I or II (based on the American Society of Anesthesiologist). Shivering was considered significant if it occurred in grade 3 or 4. Patient characteristics, shivering degree, tympanic membrane temperature, and side effects were recorded. RESULTS Shivering occurred 10% in the MgSO4 group and 19% in the meperidine group, with p = 0.23. Both groups had similar side effects of nausea, vomiting, and hypotension. CONCLUSIONS MgSO4 30 mg/kg was not superior to meperidine 0.5 mg/kg intravenously in preventing shivering in patients undergoing spinal anesthesia.